Derangement in Nicotinamide Adenine Dinucleotide Metabolism is Observed During Acute Kidney Injury Among Male Agricultural Workers at Risk for Mesoamerican Nephropathy - Nathan H. Raines; Dominic A. Leone; Juan Jose Amador; Damaris Lopez-Pilarte; Oriana Ramírez-Rubio; Iris S. Delgado; Lauren J. Francey; Jessica H. Leibler; John M. Asara; Madeleine K. Scammell; Samir M. Parikh; Daniel R. Brooks; et al. (Kidney International Reports)
Introduction: Mesoamerican nephropathy (MeN) is a chronic kidney disease (CKD) which may be caused by recurrent acute kidney injury (AKI). We investigated urinary quinolinate-to-tryptophan ratio (Q/T), a validated marker of nicotinamide adenine dinucleotide (NAD+) biosynthesis that is elevated during ischemic and inflammatory AKI, in a sugarcane worker population in Nicaragua with high rates of MeN. Methods: Among 693 male sugarcane workers studied, we identified 45 who developed AKI during the harvest season. We matched them 1:1 based on age and job category with 2 comparison groups: (i) “no kidney injury,” active sugarcane workers with serum creatinine (sCr) <1.1 mg/dl; and (ii) “CKD,” individuals no longer working in sugarcane due to their CKD, who had additional 1:1 matching for sCr. We measured urine metabolites using liquid chromatography coupled tandem mass spectrometry (LC-MS/MS) and compared Q/T and other metabolic features between the AKI and comparison groups. Results: Urine Q/T was significantly higher in workers with AKI than in those with no kidney injury (median interquartile Range [IQR]: 0.104 [0.074–0.167] vs. 0.060 [0.045–0.091], P < 0.0001) and marginally higher than in workers with CKD (0.086 [0.063–0.142], P = 0.059). Urine levels of the NAD+ precursor nicotinamide were lower in the AKI group than in comparison groups. Conclusion: Workers at risk for MeN who develop AKI demonstrate features of impaired NAD+ biosynthesis, thereby providing new insights into the metabolic mechanisms of injury in this population. Therapeutic use of oral nicotinamide, which may ameliorate NAD+ biosynthetic derangement and fortify against kidney injury, should be investigated to prevent AKI in this setting.